2003
DOI: 10.1152/ajpregu.00757.2002
|View full text |Cite
|
Sign up to set email alerts
|

The organum vasculosum laminae terminalis in immune-to-brain febrigenic signaling: a reappraisal of lesion experiments

Abstract: Romanovsky, Andrej A., Naotoshi Sugimoto, Christopher T. Simons, and William S. Hunter. The organum vasculosum laminae terminalis in immune-to-brain febrigenic signaling: a reappraisal of lesion experiments. Am J Physiol Regul Integr Comp Physiol 285: R420-R428, 2003. First published April 24, 2003 10.1152/ajpregu.00757. 2002The organum vasculosum laminae terminalis (OVLT) has been proposed to serve as the interface for blood-to-brain febrigenic signaling, because ablation of this structure affects the febr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
34
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 71 publications
1
34
1
Order By: Relevance
“…This hypothesis agrees with the fact that the anterior preoptic hypothalamus (that contains the OVLT) is more important for the control of autonomic thermoeffectors than for the control of thermotaxis (Almeida et al, 2006a) and with the fact that electrolytic lesions of the OVLT and neighboring structures readily cause hyperthermia (Romanovsky et al, 2003). We found, however, that AMG0347 fails to cause marked hyperthermia when infused via the route (intracerebroventricular) that provides good access to the OVLT and other circumventricular structures.…”
Section: Discussionsupporting
confidence: 86%
“…This hypothesis agrees with the fact that the anterior preoptic hypothalamus (that contains the OVLT) is more important for the control of autonomic thermoeffectors than for the control of thermotaxis (Almeida et al, 2006a) and with the fact that electrolytic lesions of the OVLT and neighboring structures readily cause hyperthermia (Romanovsky et al, 2003). We found, however, that AMG0347 fails to cause marked hyperthermia when infused via the route (intracerebroventricular) that provides good access to the OVLT and other circumventricular structures.…”
Section: Discussionsupporting
confidence: 86%
“…Basal thermoregulation was unaffected by the AV3V lesion. This is in contrast to a recent report in which similar lesions were found to produce a prolonged (Ͼ3 wk) hyperthermia (ϳ2°C) (26). Although we did not measure circadian temperature rhythms in these animals, T C did not differ between sham-and AV3V-lesion rats in the 30 min before exposure to the novel environment, nor was there any difference in the colonic temperature of the rats that remained in their home cage throughout protocol 2.…”
Section: Discussioncontrasting
confidence: 97%
“…Romanovsky et al (26) suggested that destruction of the AV3V region may eliminate warm-sensitive neurons within the MnPO responsible for the inhibition of thermogenesis. It is therefore possible that our slightly larger lesions restored the balance between thermolytic and thermogenic pathways in some manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations